Interval or continuous aerobic exercise performed 3 days a week increases endothelium-dependent relaxation in female rats fed with fructose - Joaquim, Anderson Gregorio; Oharomari, Leandro Kansuke [UNESP]; do Vale, Gabriel Tavares; Tirapelli, Carlos Renato; de Moraes, Camila (My University, 2022)
Aim: We investigated the effects of continuous or interval aerobic exercise training on vascular reactivity of female rats fed with fructose. Methods: Female Wistar rats (8-wk old) were divided into: sedentary (SD), continuous training (CTR), and interval training (ITR). Moderate intensity training protocols consisted of running 3 days/week for 7 weeks. CTR ran 40 min at 30%-40% of the maximal speed (MS) and TRI consisted of 7 sets of 1 min at 70% of MS followed by 3 min at 35% of MS. Animals were fed with standard chow and fructose (10%) in drinking water. Concentration-response curves to acetylcholine and phenylephrine, and oxidative stress biomarkers, were determined in the aorta. Body weight gain, visceral fat, and plasma triglycerides and glucose were also evaluated. Results: Endothelium-dependent relaxation was significantly increased by both exercise regimens (CTR: Emax = 85 ± 6% and ITR: Emax = 84 ± 1%) compared to sedentary rats (SD: Emax = 62 ± 5%). The contractile maximal response was not different but phenylephrine potency was increased in CTR (pEC50: 8.41 ± 0.19) and reduced in ITR (pEC50: 7.06 ± 0.11) compared to SD (pEC50: 7.77 ± 0.08). In addition, the generation of superoxide was lower in trained groups as compared with sedentary (about -28% in CTR and -22% in ITR). TBARS and nitrate/nitrite levels were not modified. Compared to the SD group, ITR gained 39% less body weight and CTR has 29% less visceral fat. Glucose and triglycerides were not modified. Conclusion: CTR and ITR, carried out 3 days/week, were efficient to improve endothelium-dependent relaxation and reduce superoxide generation in the aorta from female rats fed with fructose.
Keywords: endothelium; fructose; interval exercise; oxidative stress; vascular reactivity